Reverse phase high-performance liquid chromatography for quantification of hydroxymethylnitrofurazone in polymeric nanoparticles - Lis Marie Monteiro; Guilherme Diniz Tavares; Elizabeth Igne Ferreira; Vladi Olga Consiglieri; Nadia Araci Bou-Chacra; Raimar Löbenberg (Universidade de São Paulo, 2015)
Hydroxymethylnitrofurazone (NFOH) is a new compound with potential leishmanicidal and trypanocidal activity. Despite its effectiveness, the formulators have to overcome its poor aqueous solubility. Recently, polymeric nano-scale drug delivery systems have proposed for the treatment of neglected diseases. As several studies have confirmed the advantages of such formulations, and this approach provides new analytical challenges, including the need to detect trace amounts of the drug. A suitable method was developed and validated for NFOH determination bound to poly (n-butylcyanoacrylate) (PBCA) nanoparticles. The chromatographic separation was achieved using a C18 column maintained at 25 ºC and an isocratic mobile phase consisting of water and acetonitrile: 80:20 (v/v) at a flow rate of 1.2 mL min-1 and UV-detection at 265 nm. Investigated validation parameters included selectivity, linearity, accuracy, precision and robustness (changes in column temperature, mobile phase composition and flow). The method was specific, the peak of NFOH had no interference with any nanoparticle excipients and no co-elution with main degradation product (nitrofurazone). Linearity was over the range of 0.94 13.11 μg mL-1 (r2=0.999). The method was accurate and precise, recovery of 100.7%, RSD of 0.4%; intra-day and inter-day RSD range 9.98-9.99 μg mL-1 and 0.3% to 0.5%, respectively. Robustness confirmed that method could resist the applied changes. Application of the optimized method revealed an encapsulation efficiency of 64.4% (n=3). Therefore, the method was successfully developed and validated for the determination of the encapsulation efficiency of NFOH-PBCA nanoparticles.